2013
DOI: 10.1007/s00464-013-3254-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Laparoscopic Versus Open Liver Resection for Hepatocellular Carcinoma: A Case-Controlled Study with Propensity Score Matching

Abstract: The outcome of LR for HCC was technically feasible and safe in selected patients, and LR showed similar perioperative and long-term oncologic outcomes when compared with OR matched with PSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
43
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 70 publications
8
43
1
1
Order By: Relevance
“…As previously mentioned, there have been several studies that compared the long-term outcomes of LH versus OH for HCC [3,4,7,8,27], even in cirrhotic patients [9,12,29]. In addition, in this study, the OS and DFS rates were similar between the two treatment groups.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…As previously mentioned, there have been several studies that compared the long-term outcomes of LH versus OH for HCC [3,4,7,8,27], even in cirrhotic patients [9,12,29]. In addition, in this study, the OS and DFS rates were similar between the two treatment groups.…”
Section: Discussionsupporting
confidence: 65%
“…PSM offers investigators the ability to balance treated groups across all putative risk factors and allows easy inspection of the achieved balance across measured covariates [28]. To the best of our knowledge, there exists only one study of LH versus OH for cirrhotic patients with HCC using PSM [29]. However, in that report, there were differences in tumor location and type of hepatic resection (anatomical and nonanatomical resection) between the two groups after PSM.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…32 To minimize the selection biases of Lap-Hx, a case-controlled study with propensity score matching for long-term outcomes of Lap-Hx for HCC was reported. 33 However, in this study, there were originally no significant differences in the patients' background characteristics, operation time, intraoperative blood loss, need for transfusion, or tumor-related factors that could affect the patient prognoses between the 2 groups. Based on our encouraging short-term and long-term results of Lap-Hx for primary HCC within the Milan criteria irrespective of the HCC location in patients with cirrhosis, well-conducted prospective randomized controlled trials with large numbers of patients are needed to confirm our favorable results.…”
Section: Discussionmentioning
confidence: 85%
“…We therefore reviewed studies that showed the long-term outcomes of laparoscopic hepatectomy versus open hepatectomy: 2 authors showed that laparoscopic hepatectomy offered an advantage in terms of RFS [20,21] , 1 author showed slightly higher RFS at 1-2 years [22] , while the others showed no advantage in terms of RFS [23][24][25] . Unfortunately, there was little information regarding the detailed tumor location or the small number of tumors in segments 7 and 8, which were found to be associated with a high rate of AFP mRNA positivity after open hepatectomy in our study.…”
mentioning
confidence: 99%